PENYERBUKAN PADA SAGU (METROXYLON SAGU) - UTAMI, NANDA (BERITA BIOLOGI, 1986)
NANDA UTAMI. 1986.Pollination in Metroxylon sagu. Berita biologi 3(5): 229 - 231. Inflorescence morphology, flowering biology and insect visitors of sago palm (Metroxylon sagu Rottb.) were observed in Pandeglang, West Java.Sago palm is monoceous plant and self pollinated. However, insect visitors appear to play an important role for fruit setting.It was showed that the number of fruits setting in isolated inflorescence was smaller than in unisolated inflorescence.Some insect visitors recorded were Apis indica, Trigona iridipennis Ryghium haemorrhoidale.and Drosophylla melanogaster